Well‐Defined Poly(HPMAm) Brushes via Surface‐Initiated RAFT Polymerization; A Mixed‐Chain Transfer Agent (CTA) Approach - Manisha Singh; Zdeňka Sedláková; Jan Svoboda; Eliezer Jäger; Rafal Poreba (Advanced Materials Interfaces)
Abstract Over three decades, efforts to prevent non‐specific protein adsorption on surfaces have improved; however, developing well‐defined antifouling coatings remains a challenge in biomaterials research. In this study, a rapid and straightforward protocol relying on surface‐initiated reversible addition‐fragmentation chain‐transfer (RAFT) polymerization (S‐RAFT) is demonstrated to fabricate poly(N‐(2‐hydroxypropyl methacrylamide), poly(HPMAm)) brushes employing a mixed‐chain transfer agent (CTA) approach. By systematically evaluating different combinations of surface‐tethered and free CTAs, it is demonstrated that the simultaneous use of structurally distinct CTA classes; dithiobenzoate (DTB) and trithiocarbonate (TTC); enhances polymerization control and brush growth rates. The conditions enable the fabrication of poly(HPMAm) brushes exceeding 70 nm in thickness within only 4 h at 50 °C. Spectroscopic ellipsometry confirmed that the mixed‐CTA approach significantly outperforms single‐CTA systems, yielding higher polymerization efficiency and greater brush thickness. Additionally, size exclusion chromatography (SEC) confirmed that the solution‐born polymers exhibited narrow dispersity (Ð = 1.05–1.15), ensuring well‐defined polymer structures. The findings highlight the advantages of combining different CTAs in a single polymerization system, leading to a more efficient and scalable method for fabricating antifouling poly(HPMAm) coatings. This approach offers a significant potential for biomedical applications, including biosensors, blood‐contacting devices, and implantable materials.